ISSUES OF IMPROVEMENT THROUGH THE EXPERIENCE OF FOREIGN COUNTRIES IN THE DEVELOPMENT OF THE TAX CONSULTING INSTITUTE IN THE REPUBLIC OF UZBEKISTAN (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The tax advisory institute is an important institution that plays a significant role in the development of tax policy, administration, and compliance. This annotation reviews the prospects for the development of the tax advisory institute based on the literature. The literature highlights the importance of the tax advisory institute in promoting voluntary compliance, enhancing taxpayer education, providing technical assistance to taxpayers, and reducing the tax gap. The literature also identifies various challenges facing the tax advisory institute, including inadequate funding, lack of independence, and limited capacity. The review concludes by suggesting that the tax advisory institute should be adequately funded, given greater autonomy, and equipped with skilled staff and modern technology to enhance its effectiveness in providing high-quality tax advisory services.